Mapping Leadership Style and Decision-Making in Islamic Education: A Case Study of SDIT Salman Alfarisi Yogyakarta - Niswah, Afa Akmala; Rizal, Muhammad; Hidayat, Muhamad Syukron (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2025)
Purpose – This study aims to identify and map the leadership style and decision-making process implemented at SDIT Salman Alfarisi Yogyakarta, focusing on the leadership of Mrs. Fauziah Andini as the Vice Principal for Public Relations. The primary objective is to understand how spiritual values influence leadership practices, governance structures, and organizational culture within an Islamic educational institution. Design/methods – The research employed a qualitative case study approach to explore leadership dynamics in depth. Data were collected through in-depth interviews, direct observation, and document analysis, enabling triangulation and contextual understanding of leadership practices and decision-making processes. Thematic analysis was used to interpret data and construct conceptual linkages between spirituality, professionalism, and governance. Findings – The findings reveal that Mrs. Andini’s leadership harmonizes administrative competence, moral integrity, and spiritual consciousness, forming a faith-based yet professional model of leadership. Leadership is perceived as a spiritual mandate rather than a mere managerial function, characterized by collective, empathetic, and reflective decision-making. Success functions as a driver for innovation, while failure serves as an opportunity for introspection and improvement, fostering a collaborative and adaptive organizational culture. Research implications/limitations – This study highlights the transformative potential of spiritually grounded leadership in enhancing institutional effectiveness, participatory governance, and moral integrity within Islamic educational contexts. Nevertheless, its single-case design limits the generalizability of findings. Future research should adopt comparative or multi-site approaches across various Islamic schools and cultural settings to assess the broader applicability and long-term outcomes of faith-informed leadership models. Practical implications – The study suggests that leadership development programs in Islamic education should integrate spiritual intelligence, ethical reasoning, and participatory management to cultivate leaders who are both competent and morally grounded. Additionally, institutional policies should reinforce transparent communication, teamwork, and shared accountability to strengthen trust and organizational resilience. Originality/value – This research contributes to the academic discourse on Islamic educational leadership by presenting an empirical model of faith-informed leadership that integrates spirituality, professionalism, and ethical governance. It offers a unique framework illustrating how spiritual consciousness can be operationalized within modern educational management to enhance sustainability, innovation, and moral excellence in Islamic institutions.